Design and cold measurements of a coupled RFQ-SFRFQ cavity. (1st February 2022) - Wang, Z.; Tan, Q.Y.; Lu, Y.R.; Gao, S.L.; Xia, Y.; Liu, S.; Han, M.Y.; Zhao, J.
Abstract: Based on the previous research on 26 MHz coupled RFQ-SFRFQ (Radio Frequency Quadrupole-Separated-function Radio Frequency Quadrupole) cavity, we propose a higher frequency coupled RFQ-SFRFQ structure to accelerate proton beam from 35 keV to 2.5 MeV in continuous wave (CW) mode. RFQ and SFRFQ are placed in a single cavity, which greatly reduces the size of the accelerator. Instead of two RF amplifiers, only one RF amplifier is needed with this structure, as a result, this structure becomes more compact. The beam dynamic design and electromagnetic simulation have been accomplished. A 104 MHz coupled RFQ-SFRFQ aluminum model cavity has been constructed and tested at low power successfully, and the results show good agreement with the simulations.